Анализа корелације нивоа експресије сировинског молекула за адхезију ендотелних ћелија-1 и протеина сиртуин 1 код акутног респираторног дистрес синдрома: Серумски молекул за адхезију ендотелних ћелија-1 и протеин сиртуин 1 код АРДС-а - Peng, Can; Sun, Zhigang; Liu, Yanyan; Zhao, Hao (Journal of Medical Biochemistry, 2025)
Objective: To investigate the relationships among serum silencing information regulator 2-related enzyme 1 (SIRT1) expression levels, endothelial cell-specific molecule-1 (ESM-1), and fibroblast growth factor-21 (FGF21) and treatment results in patients with acute respiratory distress syndrome (ARDS) associated with sepsis. Methods: A total of 140 patients with sepsis-related ARDS were selected and divided into a good outcome group of 96 patients and a poor outcome group of 44 patients according to the treatment outcome. The levels of serum SIRT1, ESM-1 and FGF21 were compared between the two groups; the correlations between serum SIRT1, ESM-1, and FGF21 and the severity of the disease as well as the treatment outcome were analyzed; and the predictive value of serum SIRT1, ESM-1 and FGF21 for treatment outcomes was evaluated. Results: Compared to the group with a favorable outcome, the bad outcome group’s serum SIRT1 level was lower, while the ESM-1 and FGF21 levels were significantly greater than those in the good outcome group (P<0.05). Serum SIRT1 levels steadily declined in patients with mild, moderate, and severe illness, while ESM-1 and FGF21 levels steadily rose (P<0.05). ESM-1 and FGF21 showed a positive association with illness severity (P<0.05), while serum SIRT1 showed a negative correlation (P<0.05) with disease severity, according to Spearman correlation analysis. Partial correlation analysis revealed that the serum SIRT1, ESM-1, and FGF21 levels were significantly correlated with the treatment outcomes of patients with sepsis-related ARDS (P<0.05). Serum SIRT1, ESM-1, and FGF21 levels and treatment outcomes were strongly correlated (P<0.05) in patients with sepsis-related ARDS. Serum SIRT1, ESM-1, and FGF21 areas under the curve (AUCs) for predicting the course of treatment for patients with ARDS associated with sepsis were 0.742, 0.838, and 0.796, respectively. The sensitivity was 77.27%, 77.27%, and 70.45%, and the specificity was 64.58%, 81.25%, and 87.50%, respectively. For patients with sepsis-related ARDS, the combined prediction of the three markers’ AUC for treatment outcome was 0.939, with a sensitivity of 88.64% and a specificity of 83.33%, which was significantly greater than the individual predictive value of the three indicators alone (P< 0.05). Conclusion: The levels of serum SIRT1, ESM-1 and FGF21 in patients with sepsis-related ARDS are strongly connected with both the efficacy of treatment and the severity of the illness, have the ability to independently predict treatment outcomes, and have a greater combined predictive value.